The Effectiveness of Using Educational Platforms in Teaching Social Studies Subjects from Teachers' Perspectives in Light of Distance Learning - Jawdat Salameh Al-Khamaiseh (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aimed to identify the effectiveness of the educational platforms used to teach social studies subjects in the context of distance learning from the perspective of the teachers in Al-Qaser Directorate of education. The researcher used the descriptive method to fit in with the objectives of this study. The study sample consisted of 60 male and female teachers, who were selected randomly. The researcher used a questionnaire prepared specifically for the purpose of this study, which was implemented in the academic year (2020/2021). The results showed that the effectiveness of the educational platforms used in teaching social studies subjects was at an average level, with a total arithmetic average (3.02) and a standard deviation (0.21). The study also resulted in the absence of statistically significant differences between the views of the sample due to gender, academic qualification, and experience. The study recommended that work be done to develop educational platforms and technological tools commensurate with the teaching of social subjects.